PELAKSANAAN PELAYANAN PENGURUSAN AKTA KELAHIRAN DI KOTA PEKANBARU TAHUN 2011-2012 - Anshari, Riyanda Raran; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
A birth certificate is a certificate / authentic record made by civil servants in the form of an official record of the place and time of birth of a child, the child's name and the name of the child's parents are complete and clear, and the child's citizenship. Birth registration is done by the Head of the Unit of Work on the register and issued Birth Certificate Birth Certificate Kelahiran.Kutipan Deed Quotes are pelapornya done on time given to residents at no charge. In this case the birth place different from the place of residence or domicile, Magistrate of the record and issue a birth certificate Excerpt responsible notify Work Unit that manages the registration of the population and civil registration in the place of domicile. This study was conducted to investigate the implementation of public services in the birth certificate as well as to identify any obstacles encountered in the implementation of the birth certificate of service in the Department of Population and Civil Registration (Disdukcapil) Pekanbaru. The formulation of the problem as follows: How the Implementation of the Public Service in the Department of Population and Civil Registration Pekanbaru (studies obtaining a birth certificate).This study is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted in the Department of Population and Civil Registration (Disdukcapil) Pekanbaru City is located at the street Mustafa Sari No. 1, Pekanbaru. Samples that informants in this study is the head of Department and Head of the Civil Registry and the people who take care of a birth certificate in the Department of Population and Civil Registration (Disdukcapil) Pekanbaru. Data collection techniques of observation, interviews and documentation. The results of this study concluded that the implementation of the maintenance services in the city of Pekanbaru birth certificate in the category good enough, because there are not a good indication of the service given to the public servants in the management of particular birth certificate issue completion time, cost and typos on the birth certificate. The obstacles that occur in the processing of birth certificate is the resistance of the (internal) include: lack of discipline officers or officers who provide public services and physical facilities are still inadequate and the barrier from the outside (external) include awareness of society that is still lacking, especially regarding the requirements and procedures are still often overlooked by society, lack of awareness of the population to always stand in line to get service and there are many people in Pekanbaru who do not have an official marriage certificate so that the process of identifying a birth certificate lasts a little longer.Keywords: Care, Birth Certificate